Pentingnya Revitalisai Kelmaba Adat - Eko Punto Hendro (Endogami: Jurnal Ilmiah Kajian Antropologi, 2019)
The country of Indonesia, which has multi-ethnic and multi-religious communities, indeed requires the care of their customs and culture. The main treatment is aimed at building wisdom, togetherness and preventing potential social conflicts. The village is the smallest government institution in Indonesia, through the revitalization of LKD and LAD, the customs and culture of the community can be preserved, despite the great challenges in this modernization era.